Examining the influence of market orientation on costing and competitive advantage of MSMEs (International Journal of Food and Nutritional Sciences, 2022)
Market orientation is critical for small and medium-sized enterprises (SMEs) because it entails understanding customer needs and providing superior products or services. It is recognized as a driver of competitiveness and performance for MSMEs. However, limited research exists on how market orientation influences costing practices and competitive advantage in micro, small, and medium-sized enterprises (MSMEs). This study investigates the impact of market orientation on costs and competitive advantage in MSMEs. Using a quantitative research approach and a survey questionnaire, data will be collected from a sample of MSMEs in a specific industry sector.